STRATEGI KOMUNIKASI PEMERINTAH DAERAH MELALUI MEDIA SOSIAL TIK TOK - Lintang Sabilatul Arini; Arif Zainudin; Akhmad Habibullah; Gilbert Jhon (Jurnal Agregasi, 2026)
This study originated from the issue of how local governments can adjust their communication strategies to changes in community behavior, which is increasingly dependent on social media, particularly TikTok, as a means of public information. The purpose of this study is to reveal local government digital communication strategies through TikTok and the communication models used to increase community participation. The method used is a literature review with bibliometric analysis using the Scopus database as the main source, focusing on publications from 2020 to 2025, and processed through the Biblioshiny tool to map trends, themes, and research collaborations. The results of the study show that the use of TikTok by local governments has grown significantly, with fluctuating but increasing publication trends, and a shift in research focus from general issues of government communication to themes of crisis, digital literacy, and sustainability. These findings confirm the role of TikTok as a strategic medium in building adaptive, interactive, and inclusive public communication.